Explosive Target balances of the German Bundesbank - Niklas Potrafke; Markus Reischmann (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2014)
Using the recursive unit root test by Phillips et al. (2011) we show that the Target balances of the German Bundesbank have been explosive from the beginning of 2009 to the beginning of 2013. By implementing a full-allotment policy and reducing the required minimum quality of collaterals in October 2008, the European Central Bank (ECB) refinanced credits in the GIIPS countries (Greece, Ireland, Italy, Portugal and Spain) to a large extent. Private capital flowed out of the GIIPS countries, and the German Target claims increased significantly. Using the new test to identify multiple explosive periods by Phillips et al (2013) we find that the German Target claims also became explosive in autumn 2007 when the interbank market broke down for the first time.
Keywords: C22; E50; E58; F32; F34; H63; 330; Eurosystem; Target; recursive unit root test; explosiveness; hidden debt; German Bundesbank